2022
DOI: 10.1002/adma.202207829
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Engineering of Conductive Fillers toward Enhanced Dielectric Properties: A Universal Polarization Mechanism in Polymer Conductor Composites

Abstract: Flexible dielectric and electronic materials with high dielectric constant (k) and low loss are constantly pursued. Encapsulation of conductive fillers with insulating shells represents a promising approach, and has attracted substantial research efforts. However, progress is greatly impeded due to the lack of a fundamental understanding of the polarization mechanism. In this work, a series of core–shell polymer composites is studied, and the correlation between macroscopic dielectric properties (across entire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
109
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(110 citation statements)
references
References 50 publications
1
109
0
Order By: Relevance
“…GN with high electrical conductivity can increase the electrical conductivity of LVO through offering conductive highways [ 38 , 39 ]. Moreover, small LVO nanoparticles were uniformly distributed on GN to form a multi-dimensional integrated structure, building a comprehensive electron/ion transport network and stable structure, which is beneficial for the cyclic performance [ 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…GN with high electrical conductivity can increase the electrical conductivity of LVO through offering conductive highways [ 38 , 39 ]. Moreover, small LVO nanoparticles were uniformly distributed on GN to form a multi-dimensional integrated structure, building a comprehensive electron/ion transport network and stable structure, which is beneficial for the cyclic performance [ 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The lithium-ion batteries are the most mature energy storage devices at present, but their high cost and poor safety stagnate their commercial application [ 3 , 4 , 5 ]. Researchers are committed to finding products with a capacity and service life comparable to lithium-ion batteries, with lower costs and better safety performance, to satisfy the energy storage requirements of large-scale power grids in the country [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. After long-term efforts, scientists finally found that sodium-ion batteries are the most promising alternatives to lithium-ion batteries [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the thermal and electrical properties of dielectric materials can be significantly improved by adding micro or nano-scale boron nitride, alumina, carbon nanotubes, and other inorganic or organic fillers [ 18 , 19 , 20 , 21 , 22 ]. These embedded fillers with larger specific surface areas will inevitably introduce a large number of interface areas into the epoxy matrix [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%